Use of Processed Nerve Allografts to Repair Nerve Injuries Greater Than 25 mm in the Hand. (June 2017) - Rinker, Brian; Zoldos, Jozef; Weber, Renata V.; Ko, Jason; Thayer, Wesley; Greenberg, Jeffrey; Leversedge, Fraser J.; Safa, Bauback; Buncke, Gregory
Abstract : Abstract: Processed nerve allografts (PNAs) have been demonstrated to have improved clinical results compared with hollow conduits for reconstruction of digital nerve gaps less than 25 mm; however, the use of PNAs for longer gaps warrants further clinical investigation. Long nerve gaps have been traditionally hard to study because of low incidence. The advent of the RANGER registry, a large, institutional review board–approved, active database for PNA (Avance Nerve Graft; AxoGen, Inc, Alachua, FL) has allowed evaluation of lower incidence subsets. The RANGER database was queried for digital nerve repairs of 25 mm or greater. Demographics, injury, treatment, and functional outcomes were recorded on standardized forms. Patients younger than 18 and those lacking quantitative follow-up data were excluded. Recovery was graded according to the Medical Research Council Classification for sensory function, with meaningful recovery defined as S3 or greater level. Fifty digital nerve injuries in 28 subjects were included. There were 22 male and 6 female subjects, and the mean age was 45. Three patients gave a previous history of diabetes, and there were 6 active smokers. The most commonly reported mechanisms of injury were saw injuries (n = 13), crushing injuries (n = 9), resection of neuroma (n = 9), amputation/avulsions (n = 8), sharp lacerations (n = 7), and blast/gunshots (n = 4). The average gap length was 35 ± 8 mm (range, 25-50 mm). Recovery to the S3 or greater level was reported in 86% of repairs. Static 2-point discrimination (s2PD) and Semmes-Weinstein monofilament (SWF) were the most common completed assessments. Mean s2PD in 24 repairs reporting 2PD data was 9 ± 4 mm. For the 38 repairs with SWF data, protective sensation was reported in 33 repairs, deep pressure in 2, and no recovery in 3. These data compared favorably with historical data for nerve autograft repairs, with reported levels of meaningful recovery of 60% to 88%. There were no reported adverse effects. Processed nerve allograft can be used to reconstruct long gap nerve defects in the hand with consistently high rates of meaningful recovery. Results for PNA repairs of digital nerve injuries with gaps longer than 25 mm compare favorably with historical reports for nerve autograft repair but without donor site morbidity.